2016
DOI: 10.1515/jomb-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

CTX Correlation to Disease Duration and Adiponectin in Egyptian Children with T1DM/ Korelacija između CTX-a i trajanja bolesti i adiponektina kod egipatske dece sa T1DM

Abstract: SummaryBackgroundIn this study, we investigated the relationship of adiponectin with bone marker changes in Egyptian children and adolescents with T1DM and the effect of disease duration on these markers, as well as the possible correlations between adiponectin and bone markers in these patients.MethodsSixty Egyptian children and adolescent patients with T1DM were studied. Serum adiponectin and collagen breakdown products (cross-linked C-terminal telopeptide of collagen type l »CTX«) were measured and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Unhealthy diet and lack of exercise leads to obesity. The American Academy of Pediatrics recommends proper nutrition and exercise, as the first-line defence from obesity, related to prediabetes and hypertension among young people (21, 22, 23, 24). In our study, physical activity significantly affects diastolic blood pressure values ( Table VI ).…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy diet and lack of exercise leads to obesity. The American Academy of Pediatrics recommends proper nutrition and exercise, as the first-line defence from obesity, related to prediabetes and hypertension among young people (21, 22, 23, 24). In our study, physical activity significantly affects diastolic blood pressure values ( Table VI ).…”
Section: Discussionmentioning
confidence: 99%
“…As in cases of predominantly osteolytic BM in MBC, Houzé et al [93] were one of the first to study the carboxy-terminally peptide of type I collagen (CTX) as a potential bone resorption marker in urine of women with breast cancer-positive BM and observed that CTX was significantly elevated compared to healthy pre- and postmenopausal controls ( p < 0.01). Cloos et al further specified studies on CTX by differentiating isomerized, racemised, and cross-linked versions of CTX, and found that newly synthesized, ∼12 kDa, non-isomerized alpha CTX peptides (αCTX) and the cross-linked chains of αCTX (ααCTX) are preferentially released into urine of patients with BM [28, 29, 94]. Comparing urine samples of 100 women with MBC to the bone to patients with IBC without bone involvement ( n = 15) and normal controls ( n = 31), this study reported that levels were even more elevated ( p = 0.005 and p = < 0.0001, respectively) [29, 94].…”
Section: How Women With Breast Cancer Could Be Monitored (Non-invasivmentioning
confidence: 99%
“…Cloos et al further specified studies on CTX by differentiating isomerized, racemised, and cross-linked versions of CTX, and found that newly synthesized, ∼12 kDa, non-isomerized alpha CTX peptides (αCTX) and the cross-linked chains of αCTX (ααCTX) are preferentially released into urine of patients with BM [28, 29, 94]. Comparing urine samples of 100 women with MBC to the bone to patients with IBC without bone involvement ( n = 15) and normal controls ( n = 31), this study reported that levels were even more elevated ( p = 0.005 and p = < 0.0001, respectively) [29, 94]. The fact that αCTX and particularly ααCTX seem to be an interesting marker of monitor dysregulation in bone metabolism due to MBC was further supported by studies by Leeming et al, who observed that the number of distant BM ( n = 40), i.e.…”
Section: How Women With Breast Cancer Could Be Monitored (Non-invasivmentioning
confidence: 99%